2004
DOI: 10.1103/physreva.70.042716
|View full text |Cite
|
Sign up to set email alerts
|

Electron-capture cross sections of multiply charged slow ions of carbon, nitrogen, and oxygen in He

Abstract: Experimental cross sections are presented for single-and double-electron capture by C q+ , N q+ , and O q+ ͑q =2-6͒ ions from He at incident energies of ͑1.0-1800͒q eV. Measurements were performed by using a mini-electron-beam-ion-source apparatus in combination with an octopole-ion-beam-guide. The cross sections are found to vary significantly depending on the collision energy as well as on the projectile species. Some cross sections reveal minima at incident energies of a few eV/ u, below which the cross sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 41 publications
(61 reference statements)
6
37
2
Order By: Relevance
“…3 together with other available measurements and MCLZ calculations. For O 3+ -He collisions, our results are in reasonably good agreement with the experimental results of Bangsgaard et al [6] and Ishii et al [9] and show similar behavior, However, our data are considerably higher than the recommended cross sections of Janev et al [10] and found to be 60% higher than the multi-channel Landau-Zener calculations [6], based on the Taulberg expression for the coupling matrix H 12 [11]. For O 3+ + H 2 O and CO 2 collisions, the total cross sections exhibit weak energy dependence and they are almost constant with increasing impact energy, a behavior that is attributed to availability of many reaction channels that are situated nearly at the center of the reaction window.…”
Section: Total Cross Sectionssupporting
confidence: 82%
See 1 more Smart Citation
“…3 together with other available measurements and MCLZ calculations. For O 3+ -He collisions, our results are in reasonably good agreement with the experimental results of Bangsgaard et al [6] and Ishii et al [9] and show similar behavior, However, our data are considerably higher than the recommended cross sections of Janev et al [10] and found to be 60% higher than the multi-channel Landau-Zener calculations [6], based on the Taulberg expression for the coupling matrix H 12 [11]. For O 3+ + H 2 O and CO 2 collisions, the total cross sections exhibit weak energy dependence and they are almost constant with increasing impact energy, a behavior that is attributed to availability of many reaction channels that are situated nearly at the center of the reaction window.…”
Section: Total Cross Sectionssupporting
confidence: 82%
“…For O 3+ + CO 2 collisions, The MCLZ results are at least a factor of 2 smaller than the experimental results and show the same energy dependence. , present work; , Ishii et al [9]; , Bangsgaard et al [6]; , Janev et al [10]; solid line, MCLZ calculations.…”
Section: Total Cross Sectionsmentioning
confidence: 99%
“…Slow and Fast Solar Wind Parameters. Cross sections for CX between SW heavy ions and H and He are based on theoretical and experimental work of (Beijers et al 1994;Bliman et al 1992;Bonnet et al 1985;Dijkkamp et al 1985a,b;Fritsch et al 1996;Greenwood et al 2001;Harel et al 1992Harel et al , 1998Ishii et al 2004;Iwai et al 1982;Lee et al 2004;Liu et al 2005;Phaneuf et al 1987;Richter et al 1993;Shimakura et al 1992;Suraud et al 1991;Wu et al 1994 work is, however, certainly needed to improve the accuracy of the helium ionization rate of helium ).…”
Section: Hydrogen and Helium Density Gridsmentioning
confidence: 99%
“…A consequence of the electron capture process having a comparatively large collision cross-section [29] is that low intensity charge reduction peaks are frequently seen at the very low flight tube pressures used to study unimolecular decay. Evidence of this is seen in Figure 2b where residual electron capture peaks are present at laboratory-frame kinetic energies Ͼ5000 eV.…”
Section: Mike Spectra: Unimolecular and Collision-induced Dissociatiomentioning
confidence: 99%
“…Overall stability of a fully solvated metal ion may depend on the formation of an extended network of hydrogen bonds [29], and that is more easily achieved when water (up to 8 H-bonds) rather than methanol (up to 4 H-bonds) forms a four-coordinate primary solvation shell. However, much also depends on how effective structures are at using charged enhanced hydrogen bonds to lock molecules into configurations that provide more limited access to the primary shell.…”
Section: Bond Length Comparisonsmentioning
confidence: 99%